Reliģiski-filozofiski raksti, XXV - (:unkn) unknown (LU Filozofijas un socioloģijas institūts, 2019)
Religious-Philosophical Articles XXV are dedicated to the international conference Socio-Political and Religious Ideas and Movements in the 20th–21st Centuries organised by the researchers of the Institute of Philosophy and Sociology of the University of Latvia. The conference was held in cooperation with colleagues from the Institute of Political Science of the University of Opole, the Institute of International Studies of the University of Wroclaw, the Institute of General History of the Russian Academy of Sciences and the Institute of Philosophy of the St. Petersburg State University. The conference took place in Riga on 4–5 October 2018. Thus, the Institute of Philosophy and Sociology fulfilled its commitment in 2016, after the International Conference The Church and Totalitarian Regime: Secularization and Strategies of Survival, to become one of the centres for international cooperation on the topic of the Church-power relations. The conference was attended by scholars from Latvia, as well as Poland, Ukraine, Lithuania, Estonia, England and Hungary. As in 2016, the conference was attended by a large group of academics from Russia – both from the St. Petersburg State University and the institutes of Russian Academy of Sciences as well as religious educational institutions such as St. Filaret Orthodox Christian Institute. The conference served as a platform to exchange ideas and the results of the latest studies on the reciprocity and significance of religious and socio-political views and ideologies in the 20th century and nowadays. In the modern-day ever-changing political situation, increasing danger to the safety and stability of society in Latvia and other European countries is caused by the manipulation of the seemingly traditional conceptions of ethical, religious and cultural values evident in the public discourse and media space. Under the impact of global processes, social anxiety and moral disorientation facilitate a dangerous trend to trust the populist ideologies and quasi-religious ideas, as well as increase the level of radicalisation of religious communities. For a better understanding of the current processes, it is necessary to examine the experience of the 20th century, especially in the so-called ‘Soviet-bloc’ countries, where the processes of the secularisation of society took place under the circumstances of authoritarian/totalitarian regimes. Such kind of secularisation facilitated not only profoundly rooted political and social myths in society and cultivated them in the educational system and media space, but also radically changed the religious experience of believers. Looking from this viewpoint, it is crucial to establish a multidimensional understanding of the connection between the socio-political ideas and religious consciousness in society. Papers presented at the conference covered a wide range of topics connected to the above-described processes in modern society and to the retrospective analysis of the cases of the last century. The participants of the conference discussed the following issues: the interchange of socio-political ideologies and religious movements in the post-secular society; political and religious movements in the USSR (Bolshevism and the reaction of the Church towards it; the atheism and the problems of preservation of religiosity: the dissident movement and the Church; non-traditional religious groups in the circumstances of the Communist regimes); interchange of political and religious movements in Latin America (Communism and liberation theology); religion and the role of religious institutions in peace processes in the 20th–21st centuries; religion and conflicts on a global scale in the current century; the potential of religious groups in the socio-political sphere and the current tendencies and problems in the Baltic states and the EU. In Religious-Philosophical Articles XXV, we have published a part of extended texts of the papers that had been read at the conference. The authors represent different approaches and methodologies, but, at the same time, they are united by the aim to understand the complicated links between politics and religion and the mutual impact of both spheres. We are sure that the studies, published in this volume, will be of interest also to our readers.
Religious-Philosophical Articles, XXV
Keywords: Socio-Political Ideas; Inter-Confessional Dialogue; Post-Secular Society; Catholic Church; Religious Tourism; Orthodox Brotherhoods; Diaspora; Russian Orthodox Church; Pacifist Movement; KGB; Buddhism; Liberation Theology; Marxism; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::Church studies; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects